2014
DOI: 10.1007/s10554-014-0583-9
|View full text |Cite
|
Sign up to set email alerts
|

Contractile reserve in systemic sclerosis patients as a major predictor of global cardiac impairment and exercise tolerance

Abstract: Several studies have evidenced high prevalence of myocardial systolic and diastolic dysfunction among patients with systemic sclerosis (SSc). Exercise echocardiography has shown a diagnostic and prognostic role in identifying early left ventricular (LV) dysfunction in several myocardial pathological settings. The aim of our study was to evaluate early signs of LV impairment under exercise and their correlation to patient's exercise tolerance. Forty-five patients (age 60.4 ± 10.3 years) with SSc and 20 age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The present study showed that SSc patients exhibited reduced LVGLS, LVGCS and LVGRS compared with healthy controls, although some studies have had different conclusions. Cadeddu et al 20 have reported reduced LVGLS compared with controls only during exercise. Durmus et al 21 have found that LVGLS, LVGCS and LVGRS were similar between the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…The present study showed that SSc patients exhibited reduced LVGLS, LVGCS and LVGRS compared with healthy controls, although some studies have had different conclusions. Cadeddu et al 20 have reported reduced LVGLS compared with controls only during exercise. Durmus et al 21 have found that LVGLS, LVGCS and LVGRS were similar between the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…That is, impaired lung perfusion capacity reduced exercise tolerance, which affected the stroke volume without pathological heart involvement. In addition, it must be noted that diastolic dysfunction according to the E/E' ratio was reported to reduce cardiopulmonary exercise tolerance in patients with normal EF [11,18,24,25]. Therefore, the exercise tolerance is regulated by multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, the left ventricular end-diastolic volume was reported to be directly related to the change in stroke volume during exercise [17]. Cadeddu et al [18] demonstrated that bicycle exercise affected left ventricular diastolic function through global longitudinal strain using speckle tracking echocardiography, although the dysfunction was not observed at rest in systemic sclerosis. Thus, the assessment of hemodynamic function during exercise may increase heart involvement compared with at rest.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, LV hypertrophy appears more common in SSc than controls ( 52 ). Patients with SSc also have higher E/e’ ratios ( 53 ) (representing higher LV filling pressures) and increased isovolumetric relaxation times compared to controls ( 48 ). Interestingly, abnormal E/e’ ratio [defined as transmitral to mitral annular early diastolic velocity ratio ( 54 )] was also associated with duration of recognized SSc disease in months, as well as mean duration of Raynaud’s phenomenon, suggesting temporal relation in SSc-related fibrotic disease of different organs ( 49 ).…”
Section: Left Ventricular Dysfunctionmentioning
confidence: 99%